(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The phenology of Auchenorrhyncha of elm was studied in northeastem Italy; in particular potential vectors of the phytoplasma associated with elm yellows disease (EY) were considered. Tue adults of Auchenorrhyncha were monitored on elm (Ulmus minor Miller) using yellow sticky traps. Out of 38 species identified, seven are known to be vectors of phytoplasmas and three others belong to genera including vectors. Two species, Philaenus spumarius (Linnaeus) and Allygidius atomarius (Fabricius), are known vectors of the phytoplasma associated with EY. On the basis of adult phenology smμe suggestions on biologica! cycle of some leafhoppers are given.